1981
DOI: 10.1111/j.1469-8137.1981.tb01720.x
|View full text |Cite
|
Sign up to set email alerts
|

CONTROL OF DEVELOPMENT IN CHENOPODIUM ALBUM L. BY SHADELIGHT: THE EFFECT OF LIGHT QUANTITY (TOTAL FLUENCE RATE) AND LIGHT QUALITY (RED.FAR‐RED RATIO)

Abstract: SUMMARYIn nature, fluence rate and the red .far-red ratio are reduced in shadelight beneath vegetation; both show similar exponential decays with increasing canopy density. An assessment of the degree to which each of these factors controls development in natural shade was made by comparing Chenopodium album plants grown under vegetational shade with those grown under the controlled environment light treatments of low fluence rate, and combined low fluence rate and low red .far-red ratio. The observations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 28 publications
1
61
1
2
Order By: Relevance
“…Whitelam, personal communication). Although developmental effects of low R:FR ratio are most striking in stem extension, correlative effects on leaf development have been reported (Child et al, 1981;Morgan and Smith, 1981). Figure 5 shows that low R:FR ratio treatment led to a reduction in leaf area in both wild type and h:y3.…”
Section: Resultsmentioning
confidence: 92%
“…Whitelam, personal communication). Although developmental effects of low R:FR ratio are most striking in stem extension, correlative effects on leaf development have been reported (Child et al, 1981;Morgan and Smith, 1981). Figure 5 shows that low R:FR ratio treatment led to a reduction in leaf area in both wild type and h:y3.…”
Section: Resultsmentioning
confidence: 92%
“…Sparkes et al (2006) found that R:FR, rather than PAR, initiated tiller death in wheat and and Evers et al (2006) reported a relationship between R:FR and cessation of tiller appearance. As plants can detect changes in R:FR long before mutual shading takes place it seems that R:FR is acting as an 'early warning' of imminent PAR shading (Morgan and Smith, 1981;Ballaré et al, 1987) which would explain why final ear number was the same in Neu and Nat.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan & Smith (1981) found that in Chenopodium album L. reductions in PAR led to increased leaf area while reductions in R:FR resulted in increased stem extension. Stuefer & Huber (1998), working with Potentilla spp.…”
Section: Introductionmentioning
confidence: 99%
“…, 1995). Responses to reduced R : FR include rapid stem elongation with disproportionately less aboveground biomass allocated to leaves, reduced branching, greater specific leaf area, and changes in leaf shape and chlorophyll content (Morgan & Smith, 1981 ;Smith 1982 ;Weiner & Thomas, 1992 ;Schmitt & Wulff, 1993 ;Aphalo & Ballare! , 1995).…”
Section: mentioning
confidence: 99%